Clinical epidemiological characteristics and antibiotic sensitivity of Escherichia coli urinary tract infection - Zhi Wen; Jiwei Jin; Yonghong Chen; Chengjuan Zhao; Chengchun Xu; Jun Liu; Binglei Ge (PLoS ONE, 2025)
Introduction Urinary tract infections are common types of infections around the world, and most urinary tract infections are caused by Escherichia coli ( E. coli ). In order to better understand the clinical characteristics of E. coli in urinary tract infections and to guide empirical treatment, we conducted this study. Methods E. coli in hospitalized patients with urinary tract infection in 2023 was retrospectively analyzed. Urine culture was determined and analyzed for patients with urinary tract infections admitted to Xuancheng People’s Hospital from 01/01/2023–31/12/2023. More than 10 5 cfu/ml in the urine culture supernatant is of great significance to urinary tract infection. According to needs, the identification and drug sensitivity tests were carried out using standard laboratory technology and automated system of France, VITEK 2 Compact, and the Clinical Laboratory Standards Institute (CLSI) standard was adopted. Results A total of 401 strains were isolated from patients with urinary tract infections, including 62 hospital-acquired infections and 339 community acquired infections. Hospital-acquired infections were mainly ESBL-positive bacteria, and the general hospitalization time was about one month. Community acquired infections were mainly ESBL-negative bacteria. The hospital stay was about 10 days. The antibiotic susceptibility profiles were as follows: tigecycline (99.8%), imipenem (99.3%), ertapenem (99.3%), amikacin (98.3%), piperacillin/tazobactam (92.3%), cefxitin (87.3%), cefoperazone/sulbactam (85.8%), amoxicillin/clavulanate (76.6%), cefepime (76.3%), ceftazidime (75.6%), ceftriaxone (65.8%), trimethoprim/sulfamethoxazole (64.1%), ceffuroxime sodium (56.6%), cefuroximethoxazole (56.6%), and levofloxacin (21.9%). Conclusion Urinary tract infections caused by E. coli are predominantly community acquired, accounting for 84.5%(339/401), and most cases involved ESBL-negative strains. Therefore, third-generation cephalosporins remain the preferred choice for empirical treatment, while quinolones and second-generation cephalosporins are not recommended. Subsequently, the treatment regimen can be de-escalated based on confirmed infection type and patient condition, an approach that has been associated with reduced hospitalization.